DO PEER BANKS AFFECT ISLAMIC BANK FINANCIAL LEVERAGE DECISIONS? - Titi Dewi Warninda; Ay Maryani (EL DINAR: Jurnal Keuangan dan Perbankan Syariah, 2022)
This research aims to analyze the influence of peer banks on Islamic banks financial leverage decisions. The empirical model was tested using fixed-effect panel data regression with robust standard error and the data of Islamic banks in Indonesia for the years 2007-2020. The results of this study show that peer banks have a significant positive effect on Islamic bank financial leverage decisions, and it is robust during the global financial crisis. The positive impact of peer banks on Islamic bank financial leverage shows that the higher the financial leverage of the peer banks will make the Islamic bank raises its financial leverage. This research contributes to the literature and policymakers on the presence of peer banks effect, especially in Islamic bank financial leverage decisions. Islamic bank financial leverage decisions are not only affected by the circumstances of the Islamic bank itself but are also influenced by other Islamic banks' behavior.